Development Who Wants To Be A Millionaire Game For Assessment Of Cognitive Mathematics Learning Outcomes For Class 3 Elementary School: Development Who Wants To Be A Millionaire Game For Assessment Of Cognitive Mathematics Learning Outcomes For Class 3 Elementary School - Alfianita, Vinny; Wardana, Mahardika Darmawan Kusuma (Universitas Muhammadiyah Sidoarjo, 2023)
This research presents the development and evaluation of a groundbreaking 'Who Wants to Be a Millionaire' game as an innovative cognitive learning assessment tool for grade 3 elementary students. Employing the Research and Development (R&D) approach with the ADDIE model, the study underwent five crucial stages: Analyze, Design, Development, Implementation, and Evaluation. Questionnaires and documentation were used for data collection, and both qualitative and quantitative techniques were applied for analysis. The game's viability was examined by media and mathematician experts, along with grade 3 students, with impressive results, garnering